Growth inhibition by 1-deoxy-d-allulose, a novel bioactive deoxy sugar, screened using Caenorhabditis elegans assay. Issue 17 (1st September 2019) - Yoshihara, Akihide; Sakoguchi, Hirofumi; Shintani, Tomoya; Fleet, George W.J.; Izumori, Ken; Sato, Masashi
Graphical abstract: Abstract: The biological activities of deoxy sugars (deoxy monosaccharides) have remained largely unstudied until recently. We compared the growth inhibition by all 1-deoxyketohexoses using the animal model Caenorhabditis elegans . Among the eight stereoisomers, 1-deoxy-d -allulose (1d-d -Alu) showed particularly strong growth inhibition. The 50% inhibition of growth (GI50 ) concentration by 1d-d -Alu was estimated to be 5.4 mM, which is approximately 10 times lower than that ofd -allulose (52.7 mM), and even lower than that of the potent glycolytic inhibitor, 2-deoxy-d -glucose (19.5 mM), implying that 1d-d -Alu has a strong growth inhibition. In contrast, 5-deoxy- and 6-deoxy-d -allulose showed no growth inhibition of C. elegans . The inhibition by 1d-d -Alu was alleviated by the addition ofd -ribose ord -fructose. Our findings suggest that 1d-d -Alu-mediated growth inhibition could be induced by the imbalance ind -ribose metabolism. To our knowledge, this is the first report of biological activity of 1d-d -Alu which may be considered as an antimetabolite drug candidate.